Water pricing experiences in India: emerging issues - Kuppannan, Palanisami; Kakumanu, Krishna Reddy; Malik, Ravinder Paul Singh (2015)
The debate on growing water scarcity and the need to use the available water more efficiently among different sectors has once again brought in renewed focus in India. In this debate, a large part of the emphasis has been on the pricing of irrigation water, the sector which accounts for almost 80 % of the total water use but for which water is charged at a fraction of the supply cost. Low water rates, apart from encouraging the inefficient use of water, result in low revenue collections and contribute to the growing burden of government subsidies. Efforts to increase revenue collection through institutional reforms motivated mostly by international lending agencies have yielded mixed results. However, given the increasing demand for water and the resulting competition among sectors, there is scope to price water. In this context, the chapter aims to examine the issues relating to water pricing in India with a case study from Andhra Pradesh.